Проблемні питання забезпечення прав підозрюваного, обвинуваченого у кримінальному провадженні - Мартовицька, О. В.; Martovytska, O. V.; Олена Мартовицька (Supremaţia Dreptului = Верховенство Права: междунар. науч. журн. – 2019. – № 3. – С. 142-149, 2019)
Розглянуто основні тенденції наукового дослідження з питань правових та процесуальних гарантій прав підозрюваного, який обвинувачується на стадії досудового розслідування. Встановлено, що, незважаючи на певну кількість новел, які введені в КПК України 2012 року з питань удосконалення захисту прав окремих учасників кримінального провадження, все ж таки залишилися невирішеними проблемні питання, зокрема щодо захисту прав підозрюваного, обвинуваченого на стадії досудового розслідування у кримінальному провадженні. Зазначене знайшло своє відображення у проведеному дослідженні.

The article concerns the main tendencies of scientific research on the legal and procedural rights guarantees of the defendant, the suspect at the stage of the pre-trial proceedings. The current and previous law of criminal procedure of Ukraine on the issues considered in the article have been investigated, on the basis of which the comparative analysis has been carried out. The results of the analysis are used to provide improvement proposals for the current law. In addition, the inconsistence between the provisions of the Code of Criminal Procedure of Ukraine and the Law of Ukraine «On the Bar and Practice of Law» in terms of ensuring and enforcement of the right to the defense of the suspect and the defendant has been found out which causes difficulty in law enforcement. Various scientific beliefs as well as practices in the context of the research are analyzed. The authors’ assessment as well as the authors’ contemplation of the considered issues are provided. As a result, it is concluded that despite a certain number of novelties introduced in the Criminal Procedure Code of Ukraine in 2012 on the rights protection improvement of individual participants in the criminal proceedings, some alerting problems remain unsolved, in particular, the ones regarding the protection of the rights of the defendant or the suspect at the stage pre-trial investigation in the criminal proceedings. Besides, an inaccuracy in the terminology and the content of certain provisions of the Criminal Procedure Code of Ukraine is identified. The practice of the European Court of Human Rights has been studied resulting in the identification of system violations committed by the law enforcement officials and courts during the investigation of the criminal proceedings. Specific measures to prevent such violations in the future have been proposed. Specific amendments are proposed to improve the current Criminal Procedure Code of Ukraine. All mentioned aspects are reflected in the study.

Рассмотрены основные тенденции научного исследования по вопросам правовых и процессуальных гарантий прав подозреваемого, обвиняемого на стадии досудебного расследования. Установлено, что, не смотря на определенное количество новелл, которые введены в УПК Украины 2012 года по вопросам усовершенствования защиты прав отдельных участников уголовного производства, все же остались нерешенными проблемные вопросы, в частности относительно защиты прав подозреваемого, обвиняемого на стадии досудебного расследования в уголовном производстве. Указанное нашло свое отражение в проведенном исследовании.
Keywords: кримінальне провадження; criminal proceedings; уголовное производство; процесуальні гарантії прав; procedural guarantees of rights; процессуальные гарантии прав; підозрюваний; suspect; подозреваемый; обвинувачений; accused; обвиняемый